Application of the second generation intact stability criteria for fast semi displacement ships - Begovic, E.; Rinauro, B.; Cakici, F. (CRC PRESS-BALKEMA, 2020)
The Second Generation Intact Stability Criteria (SGISC) are developing since 2002 after a series of naval accidents, which clearly demonstrated that actual stability criteria are not adequate to account for significant changes in the design and operation characteristics of new commercial ships. The philosophy is a multi-level approach in which successive levels are less conservative and more accurate, arriving, if necessary, to the Direct Assessment of stability failures. In this paper, Level 1 and 2 of the three main stability failure modes of the SGISC: The Parametric Roll, Pure Loss of Stability and Surf-riding/Broaching are studied on four naval ships the Systematic Series D twoparent hulls, the ONRT, benchmark ship from research version of the US Navy, and FREMM, a class of multi-purpose French- Italian frigates. For every ship typology, when one was found vulnerable to 2nd level, the corresponding criteria were analyzed by navigation conditions to estimate operational limits.
Keywords: Science & Technology - Other Topics; Engineering